ANALISA PENCAPAIAN PROGRAM KAMPUNG KB DI KABUPATEN LAMPUNG SELATAN DENGAN SISTEM INFORMASI GEOGRAFIS - Astria Hijriani; Inas Firhan Aziz; Ossy Dwi Endah Wulansari (Jurnal Pepadun, 2022)
Efforts to realize quality family planning one of them by living in a healthy environment and also regulate natality, ideal age of childbirth and distance. Planning and Activities Programs are coordinated by representatives of the Provincial BKKBN by involving all elements in the Organizational Structure of Kampung KB (in accordance with the Decree of the Regent / Mayor) through the Forum of Deliberation or inserting in other appropriate forums. A form of realization of program planning is by the form of geographic information systems. Information about the location or place of an object located on the earth's surface and includes information on the location of geographical locations to be analyzed and made decisions. By using the Google Maps API, it is possible to use Google Maps from the geographic information system created. In its early development, the Google Maps API was limited to the Java Script API. Maps API expanded to include an infographic that makes it easy to store and interpret map-shaped data. The problem of the Department of Population Control and Family Planning related to the Kampung KB Program is that they cannot provide information anywhere where the distribution of KB Village is and what achievements have been achieved after the selection of the village into Kampung KB. The presentation of information with spatial data can be facilitated with Geographic Information System. So far, government only receives data in the form of reports of general nature, and government cannot see the distribution of Kampung KB visually. With this information can be presented Geographic Information System. In this study will be developed Geographic Information System distribution and achievement of kampung kb program. Web-based system to visualize the mapping of kb villages into the form of maps, as well as provide information about areas that have been registered as kb or non-kb villages in South Lampung Regency. The system is created using the programming languages PHP, HTML, Javascript and MySql as a system database.